2015
DOI: 10.3389/fncom.2015.00093
|View full text |Cite
|
Sign up to set email alerts
|

Subject-specific computational modeling of DBS in the PPTg area

Abstract: Deep brain stimulation (DBS) in the pedunculopontine tegmental nucleus (PPTg) has been proposed to alleviate medically intractable gait difficulties associated with Parkinson's disease. Clinical trials have shown somewhat variable outcomes, stemming in part from surgical targeting variability, modulating fiber pathways implicated in side effects, and a general lack of mechanistic understanding of DBS in this brain region. Subject-specific computational models of DBS are a promising tool to investigate the unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…This region was used as a seedpoint mask for tractography for both the lenticular fasciculus and for the thalamic fasciculus, with the globus pallidus and the thalamus used as termination masks, respectively. After generating the fiber tract trajectories, the tracts were populated with myelinated axons of 2 μm fiber diameter (FLUT length 10 μm; STIN length 57.7 μm; MYSA length 3 μm; node diameter 1.4 μm; axon diameter 1.6 μm; node length 1 μm; number lamellae 30; passive first and last nodes) using the threshold-contour mapping procedure described in [41]. Axons that overlapped with the DBS lead were removed from subsequent simulations.…”
Section: Methodsmentioning
confidence: 99%
“…This region was used as a seedpoint mask for tractography for both the lenticular fasciculus and for the thalamic fasciculus, with the globus pallidus and the thalamus used as termination masks, respectively. After generating the fiber tract trajectories, the tracts were populated with myelinated axons of 2 μm fiber diameter (FLUT length 10 μm; STIN length 57.7 μm; MYSA length 3 μm; node diameter 1.4 μm; axon diameter 1.6 μm; node length 1 μm; number lamellae 30; passive first and last nodes) using the threshold-contour mapping procedure described in [41]. Axons that overlapped with the DBS lead were removed from subsequent simulations.…”
Section: Methodsmentioning
confidence: 99%
“…While this study used a simplistic homogeneous and isotropic model of tissue conductance to obtain extracellular potential values at the axonal nodes of Ranvier, one may consider using more complex models of brain tissue with the PSO algorithm. For example, studies have shown that finite element models that incorporate inhomogeneous and anisotropic tissue properties (assigning different conductance values to various tissue types) improve modeling results and may better reflect the physiological properties of the brain [11], [32], [57]. Finally, while the implementation presented here was designed for programming a set of electrodes that have already been implanted, it is conceivable to leverage the efficiency of this approach for pre-surgical planning of DBS lead placement.…”
Section: Discussionmentioning
confidence: 99%
“…The quasistatic finite element models used for predicting tissue voltage in this study were idealized as isotropic and were homogeneous within bulk neural tissue. Increasingly complex models that more precisely model tissue conductivity using diffusion weighted imaging have been introduced in the past decade and have been shown to impact biophysical simulation results (Butson et al, 2007 ; Chaturvedi et al, 2010 ; Zitella et al, 2015 ), particularly for modeling of electrical stimulation near white matter fiber tracts (Butson et al, 2007 ; Schmidt and van Rienen, 2012 ). Further, the conductance values utilized in the tissue models presented here rely on experimentally determined values for conductance that are subject to uncertainty as evident by the range of values reported within the scientific literature (Gabriel C. et al, 1996 ; Faes et al, 1999 ).…”
Section: Discussionmentioning
confidence: 99%